The prevalence of germinal centre B-cell and nongerminal centre B-cell subtypes of diffuse large B-cell lymphomas (hans algorithm) in Hospital Sultanah Bahiyah: a comparison with modified hans and muris algorithms / Siti Shakinah Sobri - Sobri, Siti Shakinah (2020)
Diffuse large B-cell lymphoma (DLBCL) is the most common Non-Hodgkin lymphoma worldwide. It can be classified into two prognostic subgroups, germinal centre B-cell (GCB) and non-GCB (NGCB) subtypes using an immunohistochemistry (IHC) panel comprising of CD10, BCL6, and MUM1 according to Hans Algorithm (HA) while Muris algorithm (MA) incorporate BCL2 as a prognostic marker. Modified Hans (MH) used only CD10 and MUM1 in the algorithm. We had analysed 97 cases extracted from laboratory information system and review of IHC according to HA, MH and MA to determine the prevalence of DLBCL subtypes and agreement between the three and its prognostic significance. NGCB subtype predominates in HA and MH by 60.8% (59 cases) and 68.04% (66 cases) respectively but was reversed to GCB subtype, 53.61% (52 cases) when MA applied. Kappa agreement was strong, moderate, and weak for HA versus MH, HA versus MA and MH versus MA, respectively. BCL6 and MUM1 showed significant result in term of survival status (p= 0.038 and 0.002, respectively) and BCL2+ patient who did not received chemotherapy showed higher number of deaths (p=0.000). MA showed patients with NGCB subtype had inferior outcome with greater number of death (p=0.039). High agreement between HA and MH may suggest the possibility of using MH in the future but correlation with molecular profiling is recommended in the future. BCL2 had proved its prognostic significance in this study that patients may be benefited for anti-BCL2 targeted therapy.